1991
DOI: 10.1002/rsa.3240020303
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic coloring of graphs

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
214
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(215 citation statements)
references
References 5 publications
(3 reference statements)
1
214
0
Order By: Relevance
“…Concerning graphs having a fixed maximum degree, most of the results on this topic come from Alon et al [AMR90], where the following results were proved: (1) asymptotically, there exist graphs of maximum degree ∆ with acyclic chromatic number in Ω( ∆ 4 3 (log ∆) 1 3 ) ; (2) asymptotically, it is possible to acyclically color any graph of maximum degree ∆ with O(∆ 4…”
Section: Introductionmentioning
confidence: 99%
“…Concerning graphs having a fixed maximum degree, most of the results on this topic come from Alon et al [AMR90], where the following results were proved: (1) asymptotically, there exist graphs of maximum degree ∆ with acyclic chromatic number in Ω( ∆ 4 3 (log ∆) 1 3 ) ; (2) asymptotically, it is possible to acyclically color any graph of maximum degree ∆ with O(∆ 4…”
Section: Introductionmentioning
confidence: 99%
“…In Section 2, we have shown that for any fixed digraph G, the queuenumber of every L k (G) is at most the tree-queuenumber of G. Also the underlying graph of L k (G) has bounded star chromatic number, since the maximum outdegree and indegree of L k (G) are equal to those of G, respectively, and it has been shown that graphs with bounded maximum degree have bounded star chromatic number [1,10]. Thus, we have the following theorem.…”
Section: Three-dimensional Drawings Of Iterated Line Digraphsmentioning
confidence: 99%
“…Albertson and Berman mentioned in [1] that Erdős proved that a(r) = Ω(r 4/3− ) and conjectured that a(r) = o(r 2 ). Alon, McDiarmid and Reed [5] sharpened Erdős' lower bound to a(r) ≥ c r 4/3 /(log r) 1/3 and proved that a(r) ≤ 50 r 4/3 .…”
Section: Introductionmentioning
confidence: 98%